Agent and Multi-agent Technology for Internet and Enterprise Systems - Hakansson, Anne; Hartung, Ronald; Nguyen, Ngoc-Thanh (Studies in Computational Intelligence, 2010)
Research in multi-agent systems offers a promising technology for problems with networks, online trading and negotiations but also social structures and communication. This is a book on agent and multi-agent technology for internet and enterprise systems. The book is a pioneer in the combination of the fields and is based on the concept of developing a platform to share ideas and presents research in technology in the field and application to real problems. The chapters range over both applications, illustrating the possible uses of agents in an enterprise domain, and design and analytic methods, needed to provide the solid foundation required for practical systems.